Young's Modulus of Polycrystalline Titania Microspheres Determined by In Situ Nanoindentation and Finite Element Modeling. (15th December 2014) - Hao, Peida; Liu, Yanping; Du, Yuanming; Zhang, Yuefei
Abstract : In situ nanoindentation was employed to probe the mechanical properties of individual polycrystalline titania (TiO2 ) microspheres. The force-displacement curves captured by a hybrid scanning electron microscope/scanning probe microscope (SEM/SPM) system were analyzed based on Hertz's theory of contact mechanics. However, the deformation mechanisms of the nano/microspheres in the nanoindentation tests are not very clear. Finite element simulation was employed to investigate the deformation of spheres at the nanoscale under the pressure of an AFM tip. Then a revised method for the calculation of Young's modulus of the microspheres was presented based on the deformation mechanisms of the spheres and Hertz's theory. Meanwhile, a new force-displacement curve was reproduced by finite element simulation with the new calculation, and it was compared with the curve obtained by the nanoindentation experiment. The results of the comparison show that utilization of this revised model produces more accurate results. The calculated results showed that Young's modulus of a polycrystalline TiO2 microsphere was approximately 30% larger than that of the bulk counterpart.